2017
DOI: 10.18203/2349-3933.ijam20170097
|View full text |Cite
|
Sign up to set email alerts
|

The importance of HbA1C and erythrocyte sedimentation rate as prognostic factors in predicting the outcome of diabetic foot ulcer disease

Abstract: Background:The study is to determine the relation between the high HbA1c and ESR as prognostic factors with the severity of the diabetic foot ulcer disease, particularly, in predicting the final outcome in the form of higher incidence of lower extremity amputation (LEA) and/or prolonged hospital stay. The study explored the importance of increased level of serum HbA1c and erythrocyte sedimentation rate (ESR) in determining the final outcome of the disease. It revealed that the severity of diabetic foot ulcer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Revelations made from the study show that ESR levels were greater in the diabetes group than in the non-diabetic group, measuring 37.42±20.20 and 29.78±13.26 at (p<0.029) respectively. The higher ESR levels seen in diabetes patients in this study are consistent with findings of Pal et al (2017), who found comparable results in their studies. The ESR outcome of this study, however, differs from that of others, such as Heo et al (2012), who found that diabetic individuals with myocardial infarction did not have an elevated ESR, with a p-value of (p<0.20).…”
Section: Discussionsupporting
confidence: 92%
“…Revelations made from the study show that ESR levels were greater in the diabetes group than in the non-diabetic group, measuring 37.42±20.20 and 29.78±13.26 at (p<0.029) respectively. The higher ESR levels seen in diabetes patients in this study are consistent with findings of Pal et al (2017), who found comparable results in their studies. The ESR outcome of this study, however, differs from that of others, such as Heo et al (2012), who found that diabetic individuals with myocardial infarction did not have an elevated ESR, with a p-value of (p<0.20).…”
Section: Discussionsupporting
confidence: 92%
“…According to a study conducted by Bikramjit P et al, there was an increase in the ESR more than 50 mm/hour in patients with T2DM who had an HbA1c value of 7% and an increase in the ESR more than 90 mm/hour in DM patients who had an HbA1c value of more than 9%. 29 Hepcidin is a 25 amino acid peptidase hormone that inhibits iron entry into the plasma compartment through 3 sources of iron supply, namely absorption of food in the duodenum, the release of iron from macrophages and release of stored iron from hepatocytes. 30 Hepcidin is mainly produced in the liver, but hepcidin is also produced in small amounts in other tissues such as the heart, kidney, pancreas and hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all journals showed a significant decrease in HbA1c on the group intervention compared to the control group. HbA1c is an established marker to monitor diabetic status (Bikramjit, Raveender, and Sudipta, 2017). Glucose control is important for diabetics but HbA1c is the benchmark for diabetes management.…”
Section: Discussionmentioning
confidence: 99%